PARASOCIAL RELATIONSHIP, AUDIENCE COMMENTS, INFLUENCER CREDIBILITY, BRAND TRUST, DAN PURCHASE INTENTION - Vinsensia Tri Arisa; Haryono Subiyakto; Miswanto (Jurnal Akuntansi Dan Manajemen, 2026)
This study analyzes parasocial relationships, influencer credibility, audience comment moderation, and their effects on brand trust and purchase intention on TikTok. Based on data from 174 active TikTok respondents, the results show that parasocial relationships influence influencer credibility, which in turn strengthens brand trust and purchase intention. However, audience comment moderation weakens this effect. These findings underscore the importance of influencer credibility in building brand trust and influencing purchase intention, especially on a social media platform with a high level of interaction like TikTok.